2010
DOI: 10.1021/jp1043305
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Dioxide in Montmorillonite Clay Hydrates: Thermodynamics, Structure, and Transport from Molecular Simulation

Abstract: We report a Monte Carlo and molecular dynamics simulations study of carbon dioxide in hydrated sodium montmorillonite, including thermodynamical, structural and dynamical properties. In order to simulate the behaviour of a clay caprock in contact with a CO 2 reservoir, we consider clays in equilibrium with H 2 O−CO 2 mixtures under conditions close to relevant ones for geological storage, namely a temperature T =348 K, and pressures P=25 and 125 bar, and under which two bulk phases coexist: H 2 O-rich liquid o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

73
243
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(319 citation statements)
references
References 60 publications
73
243
3
Order By: Relevance
“…In addition, computer simulations have inspected the effect of water on the adsorption of carbon dioxide and methane in clay minerals, and the underlying sorption mechanisms. 16,19,20,22,26,[55][56][57][58][59][60][61] The simulated distributions confirmed that H 2 O, CO 2 , and CH 4 molecules indeed form well-defined layered structures similar to pure 1W, 2W etc. hydration states.…”
mentioning
confidence: 60%
“…In addition, computer simulations have inspected the effect of water on the adsorption of carbon dioxide and methane in clay minerals, and the underlying sorption mechanisms. 16,19,20,22,26,[55][56][57][58][59][60][61] The simulated distributions confirmed that H 2 O, CO 2 , and CH 4 molecules indeed form well-defined layered structures similar to pure 1W, 2W etc. hydration states.…”
mentioning
confidence: 60%
“…For one established slit pore, grand canonical Monte Carlo (GCMC) simulation is firstly conducted to determine the number of methane molecules stored in the pore. Details about this algorithm were introduced in the work of Botan et al 35 For all the simulations, the pressure P and temperature T of the idea reservoir are set to be 5 MPa and 298 K, respectively. In this step, 1 ns is used for reaching equilibrium.…”
Section: A Equilibrium Molecular Dynamicsmentioning
confidence: 99%
“…Molecular dynamics modeling indicates water film development on forsterite for water contents below saturation of water in scCO 2 [32]. Desiccation of clays represents a potential mechanism for creation and/or exacerbation of permeable pathways in caprock, thus posing risk to storage integrity [18,41]. Schaef et al [42] and Ilton et al [43] point out potential drying and/or expansion of clay (i.e., low iron montmorillonite saturated with Na + or Ca…”
Section: Introductionmentioning
confidence: 99%
“…Ilton et al [43] and Schaef et al [42], using in situ high pressure X-ray diffraction (XRD), observed changes in smectite clay interlayer spacing upon exposure to CO 2 at variable water content, which suggests dehydration and potential shrinkage of caprock. In contrast, using Monte Carlo and molecular dynamics simulations, Botan et al [41] investigated interlayer spacing of smectite under varying amounts of water and CO 2 , but neither shrinkage nor swelling were observed. Clay swelling against an applied pressure or under constant volume conditions and water imbibition can produce swelling pressures up to, for example, ~ 10 MPa (1450 psi) [71].…”
Section: Introductionmentioning
confidence: 99%